(3GdYWas (3KdGK bUU aj cJGH hGMOs - (3MSf, YaGa eMeOs ([(3GdbGgQI(B]s (3OGQ GdeSJbHds, 2021)
(3JMJhj Ydj eLehYI ef Gdbje hGdCNdGb GdJj JSGYO aj HfGA TNUjI CHfGAfG aj eQGMd GdYeQ GdeHcQI HCSdhH eHSW h CHWGd GdbUU YHGQI Yf eLehYg ef GdMjhGfGJ GdeYQhaI ddWad jJYde ef NdGdgG JMed GdeSFhdjIs
(3GdbWI GdJGFgI (B-- (3CQfhH hGdYeI OHOhHI (B-- (3GdTLQI GdWjHIs
(3GdJQHjI hGdWads
1 2 13 23
Keywords: (3GdCWaGds -- (3Yde GdfaSs